Examining the Effects of Leadership and Organizational Culture on Employee Performance via Work Motivation - Musdalifa, Musdalifa; Hasniaty, Hasniaty; Hamzah, M. Nasir (Universitas Muhammadiyah Makassar, 2025)
This study examines the effect of leadership style and organizational culture on employee performance, with work motivation as a mediating variable, at PT. Berkah Bersama Gemilang. Employee performance has become a critical factor in achieving organizational goals, and leadership together with organizational culture play a strategic role in shaping work motivation. A quantitative research design was applied using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, analyzed through SmartPLS 4. The population consisted of all employees of PT. Berkah Bersama Gemilang, from which 118 respondents were selected using simple random sampling. Data were collected through a structured questionnaire that had been tested for validity and reliability. The findings indicate that organizational culture significantly enhances work motivation, while leadership style shows a positive but insignificant effect. Both leadership style and organizational culture significantly improve employee performance. Furthermore, work motivation significantly contributes to employee performance and mediates the relationship between organizational culture and performance, but does not significantly mediate the relationship between leadership style and performance. These results highlight the importance of cultivating a supportive organizational culture and strengthening leadership practices to sustain employee motivation and optimize performance.